Are International Banks Different? : Evidence on Bank Performance and Strategy - Bertay, Ata Can; Demirguc-Kunt, Asli; Huizinga, Harry (World Bank, Washington, DC, 2017)
This paper provides evidence on how bank performance and strategies vary with the degree of bank internationalization, using data for 113 countries over 2000-15. The paper investigates whether international banks headquartered in developing countries behave and perform differently from those headquartered in high-income countries. The results show that, compared with domestic banks, international banks have lower valuations and achieve lower returns on equity in general. This suggests that, on average, bank internationalization has progressed beyond the point where it is in the interest of bank shareholders, potentially because of corporate governance failures and too-big-to-fail subsidies that accrue to large and complex banks. In contrast, developing country international banks seem to have benefited from internationalization compared with their high-income counterparts. Furthermore, for international banks headquartered in developing countries, bank internationalization reduces the cyclicality of their domestic credit growth with respect to domestic gross domestic product growth, smoothing local downturns. In contrast, if the international bank is from a high-income country investing in a developing country, its lending is relatively procyclical, which can be destabilizing.